If you had your birthday party on the Moon - Lapin, Joyce (Sterling Children's Books, 2019)
Introduces facts about the Moon, explaining the science behind how candles and balloons behave in the lunar atmosphere, why "moon angels" will last for thousands of years, and how gravity is different on the Moon.